1996
DOI: 10.1149/1.1837040
|View full text |Cite
|
Sign up to set email alerts
|

Study of Deposition and Dissolution Processes of Lithium in Carbonate‐Based Solutions by Means of the Quartz‐Crystal Microbalance

Abstract: The quartz crystal microbalance (QCM) was used to investigate the formation of surface films on a lithium anode. Whereas few studies have dealt directly with electrode mass changes, QCM was employed here to investigate in situ the deposition and dissolution of lithium on a Ni substrate, with respect to mass changes and changes in the surface-film morphology. The formation and destruction of the deposited surface film was followed by a real-time measurement of the resonance frequency (AD and the resistance para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 0 publications
0
37
1
Order By: Relevance
“…The results indicate that the NMC-Li-metal cell displays a large hysteresis (overpotential) over long term cycling, but the NMC-LTO and NMC-graphite cells show a stable and small overpotential. Note that the overpotential in the NMC-Li-metal cell decreases during the initial cycling, which could be explained by roughening of the surface of Li-metal providing higher surface area and lower resistance, 20 however, the overpotential increases rapidly during the continued cycling. As the NMC cathodes are cycled against different types of anodes, the differences in overpotential is assumed to be caused by the choice of the anode.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that the NMC-Li-metal cell displays a large hysteresis (overpotential) over long term cycling, but the NMC-LTO and NMC-graphite cells show a stable and small overpotential. Note that the overpotential in the NMC-Li-metal cell decreases during the initial cycling, which could be explained by roughening of the surface of Li-metal providing higher surface area and lower resistance, 20 however, the overpotential increases rapidly during the continued cycling. As the NMC cathodes are cycled against different types of anodes, the differences in overpotential is assumed to be caused by the choice of the anode.…”
Section: Resultsmentioning
confidence: 99%
“…26,27,36,37 Because ⌬f has been confirmed to be largely responsible for a mass change, 27 ⌬f irr represents the irreversible change in ⌬f at one deposition-dissolution cycle corresponding to the amount of the accumulated surface film. Figure 6 shows ⌬f irr vs. cycle number plots for Li-BETI/PC in comparison with LiPF 6 /PC, LiTFSI/PC, and LiOSO 2 CF 3 /PC.…”
Section: Region a (Thickness: < Ca 1 Nm)-inmentioning
confidence: 99%
“…We also confirmed that the high reactivity of PF 6 Ϫ anions induces the formation of LiF and has the ability to inhibit the decomposition of PC. 26,47 Because Li-BETI has very good thermal and chemical stability compared to the PF 6 Ϫ anion, 23 the chemical reactions such as 3 do not occur in the presence of BETI anions, and the formation of LiF derived via. HF (reactions 7,8,9) would not take place at the electrode surface.…”
Section: Region a (Thickness: < Ca 1 Nm)-inmentioning
confidence: 99%
“…At a more negative potential than These results indicated that the competition reaction for Nd(III)/Nd(0) reduction and IL decomposition would occur and depend on the Nd(III) concentration. The value of ηρ after 0.45 C cm −2 increased and the IL decomposition was also deduced from this result because the ηρ change implied that the quantity of the soluble species increase near the electrode and/or the viscoelastic film might be formed on the electrode surface [27,31,32,40] by the IL decomposition.…”
Section: Electrochemical Analysismentioning
confidence: 70%